2012
DOI: 10.1177/0741088312450275
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Cognitive Self-Regulation of Adolescent Struggling Writers

Abstract: This study examines the relationship between patterns of cognitive selfregulatory activities and the quality of texts produced by adolescent struggling writers (N = 51). A think-aloud study was conducted involving analyses of self-regulatory activities concerning planning, formulating, monitoring, revising, and evaluating. The study shows that the writing processes of adolescent struggling writers have much in common with "knowledge telling" as defined by Bereiter and Scardamalia (1987). Nevertheless, there ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
0
11
0
3
Order By: Relevance
“…Looking more closely at the PE students' engagement in the process of written composition, and more specifically at tasks characteristic of the planning process, it is noteworthy that in both cases, it was the PE students who made most use of these, despite their variable complexity. In this regard, it was to be expected that PE students, who apparently possessed little or no knowledge about a diversity of subjects or discourse (González, 2003), devoted more time and frequency to reading background information; however, this was not the case for drawing up an outline, a task which requires a certain degree of self-regulation that can only be achieved through experience of writing (De Milliano, Van Gelderen and Sleegers, 2012). Perhaps these results reflect the current trend -prompted by past criticisms that schools have had to face in relation to their conception of writing as a global skill based on aspects of a formal nature (grammar, punctuation, spelling, etc,) -towards extensive teaching of the processes underlying the writing task, which requires reflection on the what, how and why of writing, in other words, instilling a writing style in students which is based on planning, also referred to as an "engineering" approach (Biggs, Lai, Tang and Lavelle, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Looking more closely at the PE students' engagement in the process of written composition, and more specifically at tasks characteristic of the planning process, it is noteworthy that in both cases, it was the PE students who made most use of these, despite their variable complexity. In this regard, it was to be expected that PE students, who apparently possessed little or no knowledge about a diversity of subjects or discourse (González, 2003), devoted more time and frequency to reading background information; however, this was not the case for drawing up an outline, a task which requires a certain degree of self-regulation that can only be achieved through experience of writing (De Milliano, Van Gelderen and Sleegers, 2012). Perhaps these results reflect the current trend -prompted by past criticisms that schools have had to face in relation to their conception of writing as a global skill based on aspects of a formal nature (grammar, punctuation, spelling, etc,) -towards extensive teaching of the processes underlying the writing task, which requires reflection on the what, how and why of writing, in other words, instilling a writing style in students which is based on planning, also referred to as an "engineering" approach (Biggs, Lai, Tang and Lavelle, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Given the strong body of research demonstrating positive links between self-regulation and writing proficiency (Graham, 2006), these findings were unexpected. One explanation may be that low-achieving adolescents experience much difficulty with self-regulatory aspects of literacy practices (Bereiter & Scardamalia, 1987;De Milliano et al, 2012;Englert et al, 1988). Therefore, more self-regulation and cognitive effort may not necessarily be related to better writing proficiency norto more progression over the three grades studied.…”
Section: Discussionmentioning
confidence: 99%
“…Research into the relations between actual self-regulatory behavior and writing quality of specific tasks, for example using think-aloud procedures, is therefore needed to corroborate our findings. Interestingly, a study of De Milliano et al (2012) demonstrated that such an approach reveals that positive relationships do exist between sequential patterns of self-regulatory activities undertaken by low-achieving adolescents and their writing quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such results can be explained based on the level of complexity in both planning activities. The elaboration of a plan demands from the writer a greater degree of self-regulation, that increases with age and writing experience (De Milliano, Van Gelderen, & Sleegers, 2012), except in presence of learning difficulties, or, for example, problems with hyperactivity or attention disorders, which are the result of insufficient self-regulation (Miranda, Colomer, Fernández, & Presentación, 2012). In contrast, to reach for outside information to help with the writing process, is a habit more prominent in writers with none or little knowledge of general topics, as well as discourses.…”
Section: Second Studymentioning
confidence: 99%